2015
DOI: 10.1002/ece3.1815
|View full text |Cite
|
Sign up to set email alerts
|

European wildcat populations are subdivided into five main biogeographic groups: consequences of Pleistocene climate changes or recent anthropogenic fragmentation?

Abstract: Extant populations of the European wildcat are fragmented across the continent, the likely consequence of recent extirpations due to habitat loss and over‐hunting. However, their underlying phylogeographic history has never been reconstructed. For testing the hypothesis that the European wildcat survived the Ice Age fragmented in Mediterranean refuges, we assayed the genetic variation at 31 microsatellites in 668 presumptive European wildcats sampled in 15 European countries. Moreover, to evaluate the extent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
69
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(85 citation statements)
references
References 87 publications
12
69
2
2
Order By: Relevance
“…However, the presence of wildcats may have been missed because, for example, of different sampling effort or to local species density. Alternatively, the PO wildcat population may originate from the Iberian population, which is genetically differentiated from the German population (to which NE is connected, Mattucci et al, ) to an extent that is similar to what we observed between PO and NE (0.10 in Mattucci et al, between Fs4 and Fs5 wildcat population vs. 0.072 in this study). The PO population would thus belong to a different biogeographical unit than the NE population.…”
Section: Discussionsupporting
confidence: 88%
“…However, the presence of wildcats may have been missed because, for example, of different sampling effort or to local species density. Alternatively, the PO wildcat population may originate from the Iberian population, which is genetically differentiated from the German population (to which NE is connected, Mattucci et al, ) to an extent that is similar to what we observed between PO and NE (0.10 in Mattucci et al, between Fs4 and Fs5 wildcat population vs. 0.072 in this study). The PO population would thus belong to a different biogeographical unit than the NE population.…”
Section: Discussionsupporting
confidence: 88%
“…The subdivision of German wildcats into a central cluster and a western cluster was already indicated in three previous studies using much smaller numbers of samples and a non-continuous sampling, which was solely based on carcasses as source for genetic material Mattucci et al 2016;Pierpaoli et al 2003). In contrast to these studies, our study revealed an underlying substructure within the two major clades.…”
Section: Genetic Diversity and Substructure Within Wildcatsmentioning
confidence: 88%
“…Transferred to our study, the central and western lineage might therefore display the recolonisation from different refugia: the central lineage from the Carpathian/ Alpine region, whereas for the western lineage the Iberian Peninsula is the most likely refugia (Sommer and Nadachowski 2006). A detailed analysis combining European wildcat samples from the whole distribution range performed by Mattucci et al (2016) showed that the European wildcat populations are subdivided into five main biogeographic groups, revealing also the split in two central European populations, with divergence times from the Late Pleistocene. Future studies incorporating samples from all possible refugia have to focus on the hypothesis if the central and western lineage obtained in this study are based on recolonisation from different refugia.…”
Section: Genetic Diversity and Substructure Within Wildcatsmentioning
confidence: 93%
“…Despite being classified as “Least Concern” at global scale, the European wildcat ( Felis silvestris silvestris , Schreber, 1777) is a protected flagship species of special conservation concern in Europe, where it is strictly protected through the Bern Convention and Habitats Directive (Yamaguchi, Kitchener, Driscoll, & Nussberger, ). A recent study reported five main genetic clusters in Europe, corresponding to distinct biogeographic units (BGUs, Figure ), and all except the Iberian BGU exhibit eroded within‐cluster genetic diversity, most likely due to recent bottlenecks (Mattucci, Oliveira, Lyons, Alves, & Randi, ). These results support not only the conservation importance of the Iberian wildcat metapopulation but also suggest it was a stronghold in the recent history of the wildcat in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the recent emergence of a new variant of the rabbit hemorrhagic disease virus ( Lagovirus europaeus /GI.2) is reducing the availability the European wildcats’ main prey in the Mediterranean ecosystems (Monterroso et al., ). Another threat to the conservation of European wildcats is hybridization with con‐specific domestic cats ( F. silvestris catus ), which is documented throughout Europe (Mattucci et al., ; Yamaguchi et al., ). These recent population declines, prey scarcity and widespread hybridization, coupled with habitat degradation, depict a concerning conservation scenario for the Iberian wildcat BGU.…”
Section: Introductionmentioning
confidence: 99%